2014
DOI: 10.3748/wjg.v20.i26.8583
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative fibrinogen in patients with colon cancer

Abstract: Preoperative fibrinogen levels can serve as an independent prognostic marker to evaluate patient response to colon cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…Similar results were reported by Sun et al[35] in 255 patients with CRC and Tang et al[23] in 341 patients submitted to curative CRC surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported by Sun et al[35] in 255 patients with CRC and Tang et al[23] in 341 patients submitted to curative CRC surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Studies proved that elevated concentration of platelet count, D-dimer, and antithrombin III content had a strong association with a worse prognosis in NSCLC patients 2931. Recent studies revealed that serum fibrinogen showed a correlation with prognosis in different cancers 32,33. Elevated fibrinogen level was found to be associated with poor prognosis acting as a predictive biomarker in NSCLC patients 11,12.…”
Section: Discussionmentioning
confidence: 98%
“…Fibrinogen is transformed to fibrin by activated thrombin in the coagulation cascade, which plays an important role in the malignant process of tumor progression and metastasis . Recent studies demonstrate that plasma fibrinogen levels are associated with tumor development in several types of malignancies . Similarly, NLR has been focused on as a prognostic factor in patients with many malignancies .…”
mentioning
confidence: 99%